1991
DOI: 10.1346/ccmn.1991.0390308
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the Far-Infrared Absorption Bands of K in Micas

Abstract: Abstract--To identify the far-infrared (FIR) absorption bands related to K cations in micas, spectra of muscovite, phlogopite, and biotite were compared with the spectra of pyrophyllite and talc, which have no compensating cations, and to the spectra of micas in which K is substituted by mono-and divalent cations. Dichroic experiments using single crystals of these micas showed that some of the bands or components related to K have a strong in-plane and out-of-plane dichroic character. These experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…DISCUSSION AND CONCLUSIONS Laperche and Prost (1991) showed that K § in muscovite produces absorption bands near 110 and 140 cm J. The present pleochroic study of the FIR absorption bands of K § in muscovite shows the existence of three dichroic bands at 107, 110, and 143 cm -~.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…DISCUSSION AND CONCLUSIONS Laperche and Prost (1991) showed that K § in muscovite produces absorption bands near 110 and 140 cm J. The present pleochroic study of the FIR absorption bands of K § in muscovite shows the existence of three dichroic bands at 107, 110, and 143 cm -~.…”
Section: Resultssupporting
confidence: 55%
“…Schroeder (1990) and Prost and Laperche (1990) independently assigned the FIR absorption band near 100 cm -~ to K § in micas. Laperche (1991) and Laperche and Prost (1991) exchanged K § of micas by other cations and again assigned the FIR absorption bands near 100 and 140 cm -1 to the vibration of the compensating cations.…”
Section: Introduction Materials and Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Tateyama et al (1977) were the first to assign the strong band near 100 cm -1 in the spectra of K-bearing micas to K-O inner stretching. Farmer (1974), Prost and Laperche (1990), Laperche and Prost (1991), and Diaz et al (2000) identified two in-plane modes at 107 and 110 cm -1 and one out-of-plane mode at 143 cm -1 involving K and two double trigonal rings in muscovite, with the maximum absorption directions near b-, a-, and c*-axis, respectively. Loh (1973), Velde (1978), Roth (1978), Velde and Couty (1985), Schroeder (1990), andBoukilli et al (2001) also reported FIR spectra of micas, and Beran (2002) and Fleet (2003) reviewed FTIR work on micas, including that in the mid-IR (MIR) and FIR regions.…”
mentioning
confidence: 99%
“…Peaks below 150 cm À1 are generally assigned to vibrations of the interlayer cations or in the case of kaolinite the band at 117 cm À1 can be attributed to a vibration of the distorted Si 2 O 5 layer [20,44]. Illite and smectite have bands occurring at 88 cm À1 and 92 cm À1 respectively which have been associated with vibrations of the interlayer potassium ions [45,46]. It is evident that the illite peak at 92 cm À1 is far more intense than nearby peaks in smectite or kaolinite, suggesting that it may be possible to identify and distinguish this mineral in a clay mixture.…”
Section: Atr-fir Spectra Of Mineral Standardsmentioning
confidence: 99%